Positive effects on yield-contributing traits associated with Thinopyrum ponticum chromosome segments introgressed into durum wheat - Kuzmanović L.; Virili M. E.; Gennaro A.; Bitti A.; Ceoloni C. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
As a possible means of coping with the many challenges in today’s wheat breeding, widening of the crop genetic basis via exploitation of alien genetic variation from wild relatives is a promising and sustainable approach. Thanks to recent progress in chromosome engineering, through which alien chromosome segments can be transferred to wheat, it is now possible to target even complex traits such as those related to the yield. During the last three seasons, under Mediterranean rainfed conditions, three durum wheat-Thinopyrum ponticum near-isogenic recombinant lines with distal portions of their 7AL arm replaced by 23%, 28% and 40% of alien (= 7AgL) chromatin, respectively, containing the Lr19+Sr25+Yp genes, were included in field trials with, first, spaced plants (2 years) and then, plots (1 year) for evaluation of 7AgL-associated effects on yield-contributing traits. Overall, the results revealed the involvement of defined 7AgL portions in the increase of traits such as flag leaf width and tiller number/plant (23-28% portion), grain number/m2 and spike fertility index (28-40% portion), all traits contributing to the observed higher grain yield and biomass. Moreover, parameters measured in the plot trial (phenological phases duration, fertility at anthesis, chlorophyll content), suggested the presence in the 23-28% 7AgL region of loci significantly increasing booting-to-anthesis phase and chlorophyll content during grain filling. Conversely, the 28-40% interval was found to be associated with negative effects on biomass at anthesis and post-anthesis chlorophyll content, hence on grain filling.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)